Red meat consumption and risk of cardiovascular diseases—is increased iron load a possible link?. Issue 1 (26th January 2018) - Quintana Pacheco, Daniel A; Sookthai, Disorn; Wittenbecher, Clemens; Graf, Mirja E; Schübel, Ruth; Johnson, Theron; Katzke, Verena; Jakszyn, Paula; Kaaks, Rudolf; Kühn, Tilman
ABSTRACT: Background: High iron load and red meat consumption could increase the risk of cardiovascular diseases (CVDs). As red meat is the main source of heme iron, which is in turn a major determinant of increased iron load, adverse cardiometabolic effects of meat consumption could be mediated by increased iron load. Objective: The object of the study was to assess whether associations between red meat consumption and CVD risk are mediated by iron load in a population-based human study. Design: We evaluated relations between red meat consumption, iron load (plasma ferritin), and risk of CVD in the prospective EPIC-Heidelberg Study using a case-cohort sample including a random subcohort ( n = 2738) and incident cases of myocardial infarction (MI, n = 555), stroke ( n = 513), and CVD mortality ( n = 381). Following a 4-step mediation analysis, associations between red meat consumption and iron load, red meat consumption and CVD risk, and iron load and CVD risk were assessed by multivariable regression models before finally testing to which degree associations between red meat consumption and CVD risk were attenuated by adjustment for iron status. Results: Red meat consumption was significantly positively associated with ferritin concentrations and MI risk [HR per 50 g daily intake: 1.18 (95% CI: 1.05, 1.33)], but no significant associations with stroke risk and CVD mortality were observed. While direct associations between ferritin concentrations and MI risk as well as CVD mortality were significant in age- and sex-adjusted Cox regression models, these associations were substantially attenuated and no longer significant after multivariable adjustment for classical CVD risk factors. Strikingly, ferritin concentrations were positively associated with a majority of classical CVD risk factors (age, male sex, alcohol intake, obesity, inflammation, and lower education). Conclusion: Increased ferritin concentrations may be a marker of an overall unfavorable risk factor profile rather than a mediator of greater CVD risk due to meat consumption.